Hubungan Pengetahuan Ibu, Sikap Ibu dan Dukungan Sosial dengan Kejadian Kehamilan Resiko Tinggi di UPTD Puskesmas Batumarta VIII Kabupaten OKU Timur - Veronika Sinaga (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2021)
The number of maternal deaths in 2016 was targeted to be 138 people and 140 people were realized or 98.57 percent. This condition is then supported by the late recognition of the signs, late reaching the service point and late getting help. So, it is necessary to make optimal efforts to prevent or reduce the frequency of pregnant women who are at high risk and its handling needs to be done immediately to reduce maternal and child mortality. This study aims to determine the relationship between knowledge of mothers, mother attitudes and social support with the incidence of high risk pregnancy at Puskesmas Batumarta Viii, Oku Timur district. The method in this study using cross sectional with a population and sample of 37 respondents. Data analysis used chi square statistical test with p value ? ? value (0.05). The results of this study of 27 well-educated respondents with high risk pregnancy incidence of 26 people (96.3%) with p value = 0.01, of the 26 respondents who had a positive attitude with high risk pregnancy incidence of 25 respondents (96.2% ) p value = 0.02, from 24 respondents who supported the incidence of high risk pregnancy, 23 respondents (95.8%) p value = 0.04. Midwives are expected to increase knowledge to mothers about the signs and symptoms of high-risk pregnancies in pregnant women quickly so that the maternal mortality rate for antenatal care subscribers can be achieved according to predetermined standards.